The polybasic insert, the RBD of the SARS-CoV-2 spike protein, and the feline coronavirus - evolved or yet to evolve - Budhraja, Anshul (2021)
Recent research on the SARS-CoV-2 pandemic has exploded around the furin-cleavable polybasic insert PRRAR↓S, found within the spike protein. The insert and the receptor-binding domain, (RBD), are vital clues in the Sherlock Holmes-like investigation into the origin of the virus and in its zoonotic crossover. Based on comparative analysis of the whole genome and the sequence features of the insert and the RBD domain, the bat and the pangolin have been proposed as very likely intermediary hosts. In this study, using the various databases, in-house developed tools, sequence comparisons, structure-guided docking, and molecular dynamics simulations, we cautiously present a fresh, theoretical perspective on the SARS-CoV-2 virus activation and its intermediary host. They are a) the SARS-CoV-2 has not yet acquired a fully optimal furin binding site or this seemingly less optimal sequence, PRRARS, has been selected for survival; b) in structural models of furin complexed with peptides, PRRAR↓S binds less well and with distinct differences as compared to the all basic RRKRR↓S; c) these differences may be exploited for the design of virus-specific inhibitors; d) the novel polybasic insert of SARS-CoV-2 may be promiscuous enough to be cleaved by multiple enzymes of the human airway epithelium and tissues which may explain its unexpected broad tropism; e) the RBD domain of the feline coronavirus spike protein carries residues that are responsible for high-affinity binding of the SARS-CoV-2 to the ACE 2 receptor; f) en route zoonotic transfer, the virus may have passed through the domestic cat whose very human-like ACE2 receptor and furin may have played some role in optimizing the traits required for zoonotic transfer.